Mechanism of Anodic Dissolution of Tungsten in Sulfate–Fluoride Solutions - Martin Bojinov; Yoanna Penkova; Iva Betova; Vasil Karastoyanov (Metals)
Thin passive films on tungsten play an important role during the surface levelling of the metal for various applications and during the initial stages of electrochemical synthesis of thick, nanoporous layers that perform well as photo-absorbers and photo-catalysts for light-assisted water splitting. In the present work, the passivation of tungsten featuring metal dissolution and thin oxide film formation is studied by a combination of in situ electrochemical (voltammetry and impedance spectroscopy) and spectro-electrochemical methods coupled with ex situ surface oxide characterization by XPS. Voltametric and impedance data are successfully reproduced by a kinetic model featuring oxide growth and dissolution coupled with the recombination of point defects, as well as a multistep tungsten dissolution reaction at the oxide/electrolyte interface. The model is in good agreement with the spectro-electrochemical data on soluble oxidation products and the surface chemical composition of the passive oxide.